ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DAN PRAKTIK MANAJEMEN LABA - Rusnendar, Elan; Lestari, Ayu (LPPM UNIBI, 2020)
The purpose of this study is to examine the effect of Good Corporate Governance and Leverage to Firm Values and Earning Management. The sample of this study is companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange. The method used in determining the research sample is to use a purposive sampling method that is data collection techniques based on criteria, sample that meet the criteria are 21 companies during the 2015-2019 period. The data source used is secondary data where this research uses the annual report of the sample companies listed on the Indonesia Stock Exchange. Hypothesis testing using the t test and f test.